Simulation and Optimization of CO2 Fin-tube Gas Cooler - Wang Jing; Zhao Yuanyang; Li Liansheng; Wang Zhizhong (Zhileng xuebao)
Flow characteristics of CO2 fin-tube gas cooler have been investigated employing steady-state distribution parameter model. And the model was verified by comparing experimental data and numerical results. The influence of the inlet parameters of the CO2 side on the coefficient of heat transfer of refrigerant, the capacity of gas cooler and the pressure drop were studied. And optimization calculation was carried out. The effect of the configuration parameters and the branch number on the performance of the gas cooler was discussed. The result shows that the inlet pressure and the mass flow rate have large influence on the coefficient of heat transfer while the inlet temperature has small effect. There is an optimal inlet pressure for the capacity of gas cooler to achieve its maximum value, and the optimal inlet pressure increases with the increase of the mass flow rate. The pressure drop and the capacity of gas cooler both increase linearly with the increase of the inlet temperature. Moreover, the performance of the CO2 gas cooler can be enhanced by increasing the branch number and employing tubes of small diameter appropriately.